IJCM_334A: The struggle within: suicidal ideation and its risk factors among the undergraduate medical students - Jayasudha Jayaraman; Padmasri Y.; Mounika Ronanki (Wolters Kluwer Medknow Publications, 2024)
Background: Suicide is one of the top three causes of death among the adults worldwide, which is increasingly seen among students. Medical education is often considered highly stressful, in addition to the usual psychological issues in the youth. Mental health issue is a subject of taboo even among the medical students leading to non-help seeking behaviour. Studies report a high prevalence of suicidal ideation among medical students in India, ranging from 1.8% to 53.6%. Objectives: 1. To assess the prevalence of 'suicidal ideation' and associated risk factors among undergraduate medical students Methodology: A descriptive cross-sectional study was conducted among Phase 2 and 3 undergraduate students of a government medical college after taking IEC approval. Information on socio demographic details along with known risk factors was obtained. Beck scale for suicide ideation was used for screening and assessment of suicidal ideation. Data was analysed as proportions and percentages and chi square was applied to test the significance of association. Results: Out of the total 192 participants 118 (61.4%) were boys and 74 (38.6%) were girls. History of mental illness was present among 33 (16.6%) students. Fourteen students (7.2%) had high BSS score on screening. Within this subgroup of students reporting suicide ideation (n=14), 9 students (69.2%) had seriously contemplated suicide, while 2 students (15.3%) had attempted suicide at least once in their life time. Students who had previous history of mental illness showed higher prevalence of suicide ideation which was statistically significant (p<0.001). However, no significant associations were identified between gender of the student, mother's occupation, or a history of mental illness among family members and suicide ideation among the medical students. Conclusion: Medical students need to be assessed for their mental health and appropriate care and support should be provided to the needy to prevent fatal outcomes among them.